Peran teknologi dalam penanggulangan kemiskinan di indonesia - marwah, marwah; Marzuki, Marzuki; Uljannah, Yunita (Visi Pencerah Nusantara, 2024)
This study explores the critical role of technology in supporting poverty alleviation efforts in Indonesia. Using a Systematic Literature Review approach, this study analyzes various writings that explain the impact of the use of information and communication technology on important sectors such as education, agriculture, MSMEs, public services, and social assistance programs. The findings of this study indicate that digitalization has made processes more efficient, improved data accuracy, and provided lower-income communities with wider access to resources and economic opportunities. However, challenges remain, including the digital divide, low technological skills, and limited infrastructure. Therefore, inter-sectoral collaboration and inclusive policies are needed so that technology can truly function as an effective empowerment tool to overcome poverty sustainably in Indonesia.